The Number of Infants with Hepatitis B virus (HBV) added Each Day in India - Kapil, Umesh (Indian Journal of Community Health, 2021)
Hepatitis B virus (HBV) is one of the major global public health problems.HBV infection is the 10th leading cause of death.(1) In India, HBsAg prevalence,(an indicator of chronic HBV infection) among general population ranges from 2% to 8%.(2) HBV vaccination has been integrated in the Universal Immunization Program (UIP) for last 10 years. All new borns are expected to receive HBV vaccination at 0 day and subsequently at 6, 10 and 14 weeks. Majority of women do not know they are HBV infected. Often they do not have no symptoms. When a pregnant woman has hepatitis B, it can spread to her baby at birth. This can happen during a vaginal delivery or a c-section. Babies and young children can also get hepatitis B from close contact with family members or others who might be infected. When babies become infected with hepatitis B, they have about a 90% chance of developing a lifelong, chronic infection.